Magnetic field lights up a stellar graveyard - Safi-Harb, Samar (Nature (London), 2022)
The core of the dead star becomes a pulsar - a rapidly rotating, highly magnetized pulsating star the size of a city, which spews out a wind of fast-moving, electrically charged particles. In the past two decades, NASA's Chandra X-ray Observatory has enabled close-up views of their nebulae5, but direct imaging of the magnetic fields responsible for their high-energy radiation has not been possible. Astronomers had previously imaged magnetic fields in astronomical sources using radio and optical telescopes, but these types of radiation are subject to rotation effects and absorption by dust, respectively, both of which hinder observation. By contrast, X-ray polarization offers a direct probe of the geometry of the magnetic field in the acceleration zone, where the pulsar dumps its particle wind and emits high-energy radiation.